The Practices of Stereotyping of Black Women Scientist in Film Hidden Figures - Sri Amalia Tompunu; Magdalena Baga; Novi Rusnarty Usu (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study explores the stereotyping practices faced by Black women in the film Hidden Figures (2016), focusing on the lived experiences of three central characters—Katherine Johnson, Dorothy Vaughan, and Mary Jackson. Using feminist literary criticism and the "reading as a woman" approach, the research investigates how these women navigated and overcame institutionalized racial and gender discrimination at NASA during the 1960s. The findings indicate that prevailing stereotypes—such as assumptions of intellectual inferiority, incompetence, and submissiveness—were instrumental in marginalizing Black women within scientific spaces. However, through persistent effort, exceptional intelligence, and professional integrity, these women challenged and ultimately dismantled such stereotypes. Their success not only contributed to key space missions but also reshaped the dominant narrative around race and gender in science and technology. The study connects these fictionalized portrayals with real historical events, informed by stereotype theory, intersectionality, and existing scholarly literature. By doing so, the analysis underscores the importance of inclusive representation in media and its role in social awareness and change. In conclusion, Hidden Figures serves as a powerful narrative that reclaims Black women’s agency in history and affirms their rightful place in the scientific community.